Global supply chain: The consolidators' role - Rosa Caiazza; Tiziana Volpe; John L. Stanton (Operations Research Perspectives, 2016)
Challenges and opportunities of the global market lead agro-food small and medium firms (SMEs) to focus their source of value on production of high quality goods and implementation of flexible and robust supply chains. Despite the relevance of consolidators in the supply chain, few articles demonstrate their role in internationalization strategies of SMEs. In order to fill this literature gap, this article shows factors that affect global success of SMEs and offers some advice to decision makers.
Keywords: 330; Supply chain; Consolidator; Strategy; Agro-food; Management; Innovation